Determinants of Profitability of Indonesia Palm Oil Industry - Ali Mutasowifin; Dwitaningsih Dwitaningsih (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
Palm oil is one of Indonesia's leading sectors. Palm oil companies on the IDX experi-enced a decline in profitability from 2016-2019. Some even had negative profits. One indicator to assess the company's performance is to look at the level of profitability. This study aims to analyze the effect of leverage, activity, liquidity, and sales growth on the profitability of palm oil companies for the 2016-2020 period. The sampling method used is non-probability sampling with a purposive sampling technique. This study uses panel data regression analysis. The results showed that Debt to Asset Ratio, Total Asset Turnover, and Current Ratio had a negative effect on ROA, while Working Capital Turnover had no effect on ROA, and sales growth had a positive effect on ROA.